2018
DOI: 10.1101/396564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced resistance to bacterial and oomycete pathogens by short tandem target mimic RNAs in tomato

Abstract: Nucleotide binding site leucine-rich repeat (NLR) proteins of the plant innate immune system are negatively regulated by the miR482/2118 family microRNAs (miRNAs) that are in a distinct 22nt class of miRNAs with a double mode of action. First they cleave the target RNA, as with the canonical 21nt miR-NAs, and second they trigger secondary siRNA production using the target RNA as a template. Here we address the extent to which the miR482/2118 family affects expression of NLR mR-NAs and disease resistance. First… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…In such cases, blocking or overexpressing a single miRNA can achieve up-or down-regulation of multiple genes, facilitating gene manipulation when these target genes have functional redundancy. For example, in tomato, blocking miR482 and miR2118 via STTM resulted in increased resistance to at least two different pathogens (Canto-Pastor et al 2019). Therefore, it would be worthwhile investigating the roles of miRNAs in rice-M. oryzae interaction and applying them to breeding programs to improve agronomic traits such as disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, blocking or overexpressing a single miRNA can achieve up-or down-regulation of multiple genes, facilitating gene manipulation when these target genes have functional redundancy. For example, in tomato, blocking miR482 and miR2118 via STTM resulted in increased resistance to at least two different pathogens (Canto-Pastor et al 2019). Therefore, it would be worthwhile investigating the roles of miRNAs in rice-M. oryzae interaction and applying them to breeding programs to improve agronomic traits such as disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…RPPL1 (Putative disease resistance RPP13-like protein 1) and 205D04_12 (TIR-NBS-LRR disease resistance protein) are known to be related to plant defense responses. Canto-Pastor et al [46] reported that disease resistance protein (TIR-NBS-LRR class), retrovirus-related Pol polyprotein from transposon TNT 1-94 (KK1_048795), and transposon Ty3-I Gag-Pol polyprotein (KK1_043666) were targets of miR482/2118 members and they could affect expression of nucleotide binding site leucinerich repeat (NLR) mRNAs and disease resistance. NLR proteins of the plant innate immune system had a role in quantitative disease resistance in addition to dominant gene resistance that has been well characterized [46,47].…”
Section: Gwas and Genes Associated With Diseasesmentioning
confidence: 99%
“…Canto-Pastor et al [46] reported that disease resistance protein (TIR-NBS-LRR class), retrovirus-related Pol polyprotein from transposon TNT 1-94 (KK1_048795), and transposon Ty3-I Gag-Pol polyprotein (KK1_043666) were targets of miR482/2118 members and they could affect expression of nucleotide binding site leucinerich repeat (NLR) mRNAs and disease resistance. NLR proteins of the plant innate immune system had a role in quantitative disease resistance in addition to dominant gene resistance that has been well characterized [46,47]. Signal transducer and activator of transcription A (LOC107484292) was identified with gene expression regulation related functions within the genome-wide significant association regions on LGB08, which had similar function with STAT1 in mammals (Additional file 8: Table S6).…”
Section: Gwas and Genes Associated With Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In dicots and gymnosperms, miR482/2118 members co-ordinately regulate many nucleotide-binding site leucine-rich repeat (NBS-LRR) disease resistance genes by targeting their conserved P-loop domains (Zhai et al, 2011;Li et al, 2012;Shivaprasad et al, 2012;Zhu et al, 2013;Xia et al, 2015;Canto-Pastor et al, 2019), and are thought to be continually co-evolving with their resistance gene targets (Gonzalez et al, 2015;Zhang et al, 2016). miR482/2118 post-transcriptionally represses the transcript levels of NBS-LRR genes, but upon infection with viral, bacterial and fungal pathogens, miR482/2118 levels are themselves repressed to relieve the suppression of their target disease resistance genes (Shivaprasad et al, 2012;Zhu et al, 2013;Canto-Pastor et al, 2019), suggesting a critical role for the miR482/ 2118-NBS-LRR regulatory module in the balance of disease resistance and fitness of plants. Like most other plants, cotton contains hundreds of NBS-LRR genes with approximately 12% of them being targets of miR482/2118 (Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%